(untitled) (Journal of Hama University, 2024)
one of the important problems in engineering management that has a very big number of solutions is selecting designs of steel warehouses (that are capable to be disassembled and assembled) of mobile plant for buildings demolition resultants recycling in case that the group of adopted designs of warehouses (for example three adopted designs for three warehouses in a location) is the same in all locations that the mobile plan will locate in, In order to get the minimum cost of the warehouses in the conditions of steel element limitations. The genetic algorithms theory is considered as one of the best mathematical methods which are used to find the optimum solution of problems that have a very big number of solutions. In this research we will fit genetic algorithms and automation to be capable of solving the problem mentioned above where the components of the problem are expressed by suitable model and we will show the properties of genetic algorithms and automation that was used to deal with this problem.